The emergence of boredom in an online language class: An ecological perspective. (July 2022) - Kruk, Mariusz; Pawlak, Mirosław; Elahi Shirvan, Majid; Shahnama, Mojdeh
Abstract: Although research into boredom has gained popularity in traditional, in-person English classes over the past few years, still little is known about this context-bound, aversive, and multifaceted emotion in other settings such as those prompted by the sudden COVID-19 outbreak. With this gap in mind, and given the situated nature of boredom, in this study we explored the emergence of boredom under the influence of different ecosystemic factors via the nested ecosystems models. In order to do so, we selected four intermediate-level learners to participate in this study. They took part in two semi-structured interviews, one at the start and one in the middle of the semester. The collected data were qualitatively analyzed and coded through MAXQDA (Version 2020), based on the nested ecosystems model. The findings provided evidence for the emergence of boredom under the influence of different ecosystemic factors. At the microsystem level, the following issues were identified: technological, teacher's teaching style, class control, participants and peers, the use of online tools, and class assignments and activities. At the mesosystemic level, the factors responsible for boredom included past and current learning experiences and home issues. Finally, at the exosystemic level they encompassed curriculum design, online platform problems and learners' literacy of using the online platform.